Stage-Stratified Analysis of Prognostic Significance of Bax-Interacting Factor-1 Expression in Resected Colorectal Cancer. (23rd September 2013) - Ko, Yoon Ho; Cho, Young-Seok; Won, Hye Sung; An, Ho Jung; Sun, Der Sheng; Hong, Soon Uk; Park, Jin Hee; Lee, Myung Ah
Abstract : Background/Aim. Bax-interacting factor-1 (Bif-1) plays a crucial role in apoptosis and autophagy. The aim of this study was to evaluate Bif-1 protein expression and its prognostic significance in colorectal cancer (CRC). Methods. We analyzed Bif-1 protein expression in 251 resected specimens from patients with CRC by immunohistochemistry using tissue microarray. Results. Low Bif-1 expression was observed in 131 patients (52.2%) and high Bif-1 expression in 120 patients (47.8%). No significant differences were observed in clinicopathological parameters between patients with high and low Bif-1 expression. Kaplan-Meier survival analysis showed no difference in survival between patients with high and low Bif-1 expression. Stratified analysis of Bif-1 according to TNM stage demonstrated that low Bif-1 expression was significantly associated with a poor outcome in patients with stages I and II (P = 0.034 ). Stratified multivariate analysis demonstrated that low Bif-1 expression was an independent indicator of poor prognosis (hazard ratio, 0.459; 95% confidence interval, 0.285–0.739; P = 0.001 ). Conclusion. Patients with low levels of Bif-1 expression have shortened survival rates in CRC of stages I and II. This suggests that Bif-1 protein expression may be a useful prognostic marker in early-stage CRC.